Thermoelectric Properties of Polymeric Mixed Conductors. (4th July 2016) - Ail, Ujwala; Jafari, Mohammad Javad; Wang, Hui; Ederth, Thomas; Berggren, Magnus; Crispin, Xavier
Abstract : The thermoelectric (TE) phenomena are intensively explored by the scientific community due to the rather inefficient way energy resources are used with a large fraction of energy wasted in the form of heat. Among various materials, mixed ion‐electron conductors (MIEC) are recently being explored as potential thermoelectrics, primarily due to their low thermal conductivity. The combination of electronic and ionic charge carriers in those inorganic or organic materials leads to complex evolution of the thermovoltage ( V oc ) with time, temperature, and/or humidity. One of the most promising organic thermoelectric materials, poly(3, 4‐ethyelenedioxythiophene)‐polystyrene sulfonate (PEDOT‐PSS), is an MIEC. A previous study reveals that at high humidity, PEDOT‐PSS undergoes an ionic Seebeck effect due to mobile protons. Yet, this phenomenon is not well understood. In this work, the time dependence of the V oc is studied and its behavior from the contribution of both charge carriers (holes and protons) is explained. The presence of a complex reorganization of the charge carriers promoting an internal electrochemical reaction within the polymer film is identified. Interestingly, it is demonstrated that the time dependence behavior of V oc is a way to distinguish between three classes of polymeric materials: electronic conductor, ionic conductor, and mixed ionic–electronic conductor. Abstract : Monitoring the time dependence of the thermovoltage ( V oc ) is a way to distinguish between three classes of polymeric materials: electronic conductor, ionic conductor, and mixed electronic–ionic conductor. In case of a mixed ionic–electronic conductor, poly(3, 4‐ethyelenedioxythiophene)‐polystyrene sulfonate (PEDOT‐PSS), electrical, and spectroscopic evidence show the presence of an internal electrochemical reaction induced within the conducting polymer layer promoted by the ionic thermoelectric effect.